Our Founders - article editotial (Литьë и металлургия)
RUP "Belarussian metallurgical works"GNU Institute of metals technology of the National Academy of Sciences of RBNP RUP Institute BelNIIlitRUP Gomel foundry "TsentrolitRUMP "Kuzlitmash"